Physicochemical and Nutritional Characterization of Starch Isolated from Colocasia antiquorum Cultivated in Oaxaca, Mexico - Karina Ríos-Ríos; Edith González-Mondragón; Maira Segura-Campos; Mariela Ramírez-Jiménez; Jesús López-Luna; Irma López-Martínez; David Betancur-Ancona (Journal of Chemistry)
The physicochemical and nutritional characteristics of Colocasia antiquorum (taro coconut or Chinese taro) starch cultivated in Oaxaca, Mexico, were determined. The granules of Colocasia antiquorum presented a truncated ellipsoidal shape. The chemical composition analysis showed levels of moisture, ash, protein, fat, fiber, and NFE in a dry base of 10.29, 0.18, 2.0, 0.05, 0.01, and 97.76, respectively, as well as amylose and amylopectin contents of 13.05 and 86.95%, respectively. Gelatinization temperatures, onset (To), peak (Tp), and final (Tf), were 72.86, 82.91, and 93.05°C, respectively. Solubility, swelling power (SP), and water absorption capacity (WAC) correlate directly with increments in temperature. Transmittance value (% T) for taro coconut was 0.3% and its apparent viscosity ranged from 100 to 150 cp. The nutritional characterization of Colocasia antiquorum’s starch amounted to 97.88% of total starch (TS), while available (AS) and resistant starch (RS) were 93.47 and 3.70%, respectively. Colocasia antiquorum, grown in Oaxaca, Mexico, is an unconventional source of starch with added value due to its potential use as an ingredient in the development of new products or as a substitute for conventional starch sources in industrial processes.